Relocation of Alona manueli Sinev & Zawisza 2013 and a new closely related species from the Ecuadorian Andes to the new genus Alpinalona (Cladocera, Chydoridae, Aloninae) - Alonso, Miguel; Sinev, Artem Y. (Zootaxa, 2017)
Alpinalona gen. nov. is described for two species found in high altitude localities of continental North America and South America: Alona manueli (Sinev & Zawisza, 2013) from the Neovolcanic Mexican Axis and Alpinalona cajasi gen. et sp. nov from El Cajas National Park (Ecuador). The new genus is separated from Hexalona and allies by the absence of limb VI and filter plate V; from Anthalona, Coronatella and the elegans-group by having seven setae on exopodite III, and by the presence of a well-developed seta 1 on the IDL of limb III; from Alona s. str. (quadrangularis-group) and Ovalona, by two main head pores, lateral head pores located close to main pores, and by a bilobed exopodite V; from Ovalona by the presence of seta (i) and inner setae 2–3 on limb I, and setae 4–5 of exopodite III being of same size; and from Alona s. lato by weakly developed marginal denticles of postabdomen, clusters of thin setulae on ventral surface of limb I, and by plumose setae 5–6 of exopodite IV. Alpinalona cajasi sp. nov. can be easily distinguished from A. manueli by the following characteristics: prominent posterodorsal angle of carapace; broader headshield; longer PP distance; and postanal marginal denticles organized into groups.